2023
DOI: 10.1021/acsanm.3c00043
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fabrication of Electrodes on Graphene Oxide–MXene Composites for Planar Supercapacitors

Abstract: Graphene-based supercapacitors are powerful devices for supporting smart wearable electronics. However, the properties of the as-prepared graphene and its analogues differ from the expected characteristics, which hinder the development of graphene-based energy storage devices. Herein, we demonstrated the fabrication of planar supercapacitors based on laser-induced electrostatic self-assembled graphene oxide−MXene (GO−M) composites. Owing to the synergetic effect of the laser−matter interaction and electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[220] Mentioning laser patterning of GO, in recent works, MXenes have often been combined with graphene-based materials for SCs. [221,222] Laser scribing of MXenes/graphene has proven to be useful not only for energy-related applications but also for sensors, ranging from simple pressure sensors to more complex wearable platforms. For instance, Zhao et al [175] reported a pressure sensor fabricated by patterning a MXene/GO film on a flexible polydimethylsiloxane (PDMS) substrate using a CO 2 laser.…”
Section: Laser Scribing Of Mxenesmentioning
confidence: 99%
“…[220] Mentioning laser patterning of GO, in recent works, MXenes have often been combined with graphene-based materials for SCs. [221,222] Laser scribing of MXenes/graphene has proven to be useful not only for energy-related applications but also for sensors, ranging from simple pressure sensors to more complex wearable platforms. For instance, Zhao et al [175] reported a pressure sensor fabricated by patterning a MXene/GO film on a flexible polydimethylsiloxane (PDMS) substrate using a CO 2 laser.…”
Section: Laser Scribing Of Mxenesmentioning
confidence: 99%
“…Among various TMOs (MnO 2 , 13 NiO, 14 MoO 3 15 ), TiO 2 emerges as an attractive material for this purpose due to its cost-effectiveness, abundance, efficient charge transport pathways, high chemical stability, nontoxic nature, and environmental friendliness. 16 In this paper, we report a facile process for fabricating the porous carbon nanofibers bearing as-prepared TiO 2 hollow nanospheres (hTiO 2 ) electrodes using electrospinning followed by heat treatment for the first time. This process can increase the porosity and surface area of CNFs through the uniform distribution of hTiO 2 , which ultimately improves the specific capacitance of supercapacitor electrodes.…”
Section: Introductionmentioning
confidence: 99%